Water and Diabetes: Prevention and Cure - Sanjay Kalra; Navneet Agrawal; Nitin Kapoor (Journal of the Pakistan Medical Association)
Water is ubiquitous in nature, and that is why, perhaps, it is not viewed as a nutrient. In the context of diabetes, water intake may have implications in increasing insulin resistance, development of complications, relation to anti-diabetic agents and also in prevention of diabetes.